Obstacles to the multi-story structural metal structures in the State of Kuwait and ways to develop them: مُعـوقات الإنشاءات المَعـدَنية الهيـْكـلِية مُتعَـددِة الطَـوابقْ في دَولة الكِويت وَسُبل تَطـويرْها - Abdulrahman Musaed Abdulrahman Albannai (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
The aim of the research is to identify the obstacles that hinder the spread and development of multistory metal structures in the State of Kuwait by following the analytical approach to the actual status of this type of constructions and the problems that are encountered through studies, researches and approved government reports and through a field visit to the relevant authorities and statistics From the concerned authorities and discussing the obstacles to not adhering to the standards and specifications of the Kuwaiti construction code and its impact on the design and the high cost of construction and reducing the shelf life of the buildings. Since steel is the basis of these installations, talking about it is essential concerning the methods of formation and related manufacturing industries, and the obstacles facing this industry, and consequently, have a direct impact on the multistory metal plant industry, and the research also touched on the national technical cadres, which are required to advance this industry. Since the Kuwaiti climate has an impact on construction, it was necessary to address the effects of this on metal establishments and the importance of cultural identity and cultural heritage for the Kuwaiti citizen, it was necessary to address the extent to which these facilities are suitable for this legacy and ended with a visualization of the desired mineral construction status through the presentation of simple examples of construction multistory metal in external countries.